PENGARUH MOTIVASI DAN MODAL PSIKOLOGI TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA (Studi pada Dinas Kesehatan Kota Semarang) - Puguh Priyambodo, 12.5202.0209; Rijanti, Tristiana (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to determine the influence of motivation, psychological capital on job satisfaction, motivation, psychological capital and job satisfaction on employee performance motivation, psychological capital and job satisfaction on employee performance in Semarang City Health DepartemenÂ mediated by job satisfaction. The total sample of 147 employees. Intake samples was done by the technique